Hospitalization of unintentional fall injuries in Kuwait: a national database study - Islam Kamal Ibrahim; Fatima AlAsoomi (BMC, 2021)
Abstract Background Accidental falls are a major cause of morbidity placing pressure on hospital capacity and utilizing costly services. Evaluating the burden of falls is key for planning, implementation, and evaluation of prevention strategies. To date, no studies have been published on accidental falls at the population level in Kuwait. We studied the burden of accidental falls on public hospital inpatient capacity in Kuwait and identified the subgroups with the highest utilization of inpatient service days. Methods From the national database of inpatient hospitalizations, we selected hospitalizations of patients admitted to Kuwait's public hospitals for unintentional injury caused by an accidental fall from 1 January through 31 December 2016. We studied the number of inpatient service days (bed days), length of stay (LOS), and number of hospitalizations by age group, gender, and nationality. Mann-Whitney, Kruskal-Wallis, and Chi square tests were used for comparison. Logistic regression was used to quantify the risk of prolonged LOS and fractures among fall-related hospitalizations. Results Accidental falls were responsible for 2.9% of inpatient hospitalizations, 3.7% of inpatient service days (61,140 days) with an ALOS of 9.1 days in Kuwait's public hospitals in 2016. Accidental falls were responsible for 4.6% of older adult service days, and an even higher 5.6% of older women service days. In the age group 13-64, fall-related service days for non-Kuwaitis (5.7%) were more than triple those for Kuwaitis (1.8%) with a substantial percentage among male non-Kuwaitis (8.1%). The risk factors for exceeding the national ALOS for fall-related hospitalizations were female gender (OR 1.36), age 65 and older (OR 9.72), age 13-64 (OR 5.20), being non-Kuwaiti (OR 1.39), sustaining a femur fracture (OR 11.67), and undergoing surgery (OR 2.63). Fall-related hospitalizations associated with a higher risk of fractures were females (OR 1.22), patients 65 years and older (OR 5.09), patients aged 13-64 (OR 3.65), and non-Kuwaitis (OR 1.28). Conclusions Accidental falls impose a considerable burden on inpatient service utilization in Kuwait. This varies by age, gender, and nationality. To reduce this burden, prevention programs should target working-age non-Kuwaiti males and older females.